2010
DOI: 10.1128/jvi.02590-09
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Induces the K48-Linked Polyubiquitination and Proteasomal Degradation of Target Cellular Proteins To Activate ATR and Promote G 2 Arrest

Abstract: HIV-1 viral protein R (Vpr) induces cell cycle arrest at the G 2 /M phase by a mechanism involving the activation of the DNA damage sensor ATR. We and others recently showed that Vpr performs this function by subverting the activity of the DDB1-CUL4A (VPRBP) E3 ubiquitin ligase. Vpr could thus act as a connector between the E3 ligase and an unknown cellular factor whose ubiquitination would induce G 2 arrest. While attractive, this model is based solely on the indirect observation that some mutants of Vpr reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 61 publications
1
46
1
Order By: Relevance
“…However, we also note a further caveat that should be borne in mind. Most of the data published on the mechanism of Vpr-mediated cell cycle arrest, as well as the data presented here, have been obtained by transient transfection or ectopic expression of Vpr (3,4,11,13,14,27,28). The levels of HIV-1 Vpr incorporated into incoming particles have been shown to be sufficient to induce some G 2 /M arrest (27), and of course de novo expression in the infected cells does this robustly.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we also note a further caveat that should be borne in mind. Most of the data published on the mechanism of Vpr-mediated cell cycle arrest, as well as the data presented here, have been obtained by transient transfection or ectopic expression of Vpr (3,4,11,13,14,27,28). The levels of HIV-1 Vpr incorporated into incoming particles have been shown to be sufficient to induce some G 2 /M arrest (27), and of course de novo expression in the infected cells does this robustly.…”
Section: Discussionmentioning
confidence: 97%
“…Although several putative Vpr targets have been described, the identity of that which triggers this event has until recently remained elusive. The requirement for the ubiquitin-proteasome system and, in particular, K48-ubiquitin linkages supported a notion that the Vpr target is degraded (14). However, Laguette and colleagues recently found that Vpr interacts with the SLX4 complex, members of the Fanconi anemia DNA repair pathway (15).…”
mentioning
confidence: 92%
“…Specifically, different effects have been described for different types of polyubiquitin chains; for example, the K48 polyubiquitin (polyUb) chain is recognized by, and promotes degradation of proteins through, the proteasome, whereas the K63 polyUb chain promotes autophagic clearance of oligomeric and aggregated proteins. [23][24][25] We found that progerin is preferentially ubiquitinated by K63-linked polyUb chains, suggesting that it is a substrate for autophagy. Additionally, progerin co-immunoprecipitates with the autophagic adaptor protein p62, further demonstrating that the clearance of progerin is mediated by autophagy.…”
Section: Rapamycin Promotes Clearance Of Progerinmentioning
confidence: 95%
“…However, the detailed mechanism of Vpr-induced G 2 /M arrest is not yet clear. Several lines of evidence suggest that G 2 arrest requires interaction of Vpr with the CRL4 E3 ubiquitin ligase complex, comprising DDB1, CUL4, and RBX1, via its cellular partner DCAF1 (22)(23)(24)(25)(26)(27)(28)(29)(30). DCAF1 is a substrate receptor component of the CRL4 (31)(32)(33).…”
mentioning
confidence: 99%